1992
DOI: 10.2527/1992.7061760x
|View full text |Cite
|
Sign up to set email alerts
|

A bioeconomic simulation model for a hierarchical swine breeding structure

Abstract: A stochastic computer model was developed to simulate individual pigs in a hierarchical breeding system. The bioeconomic model was designed as a tool to facilitate the evaluation of selection, culling, and management strategies for a three-tiered breeding structure. Events such as mating, farrowing, and selection occurred weekly. Variables included number of pigs born alive, survival rate from birth to weaning, average daily gain and backfat at 110 kg, number of pigs weaned, feed per gain, days from weaning to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…General Approach. Systems of parity culling levels for a 10-yr planning horizon were simulated using the three-tiered stochastic swine life-cycle model described by Faust et al (1992b). Briefly, the model simulated production of market hogs from a three-breed, static crossing scheme and consisted of three distinct nucleus populations (maternal grandam, maternal grandsire, and terminal sire), a multiplier tier producing F1 gilts, and a commercial tier.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…General Approach. Systems of parity culling levels for a 10-yr planning horizon were simulated using the three-tiered stochastic swine life-cycle model described by Faust et al (1992b). Briefly, the model simulated production of market hogs from a three-breed, static crossing scheme and consisted of three distinct nucleus populations (maternal grandam, maternal grandsire, and terminal sire), a multiplier tier producing F1 gilts, and a commercial tier.…”
Section: Methodsmentioning
confidence: 99%
“…All boars that were not removed for involuntary reasons were culled after 11 wk of service. Involuntary culling for sows was described by Faust et al (1992b) and resulted in an annual rate of approximately 10% (excluding mortality and barrenness rates). Maximum sow parities within each tier were determined by the experimental design with combinations of 1-and 5-parity nucleus and 1-, 5-, and 10-parity multiplier and commercial strategies (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Simulation models have been used to examine the effect of culling rate, replacement gilt cost and other factors on the profitability of commercial swine operations. Faust et al (1992Faust et al ( , 1993a developed simulation models of swine breeding system to evaluated various effects, including culling, on profitability. The simulation models demonstrated that systems with the lowest commercial replacement rates (i.e.…”
Section: Economic Importancementioning
confidence: 99%